Analyzing the Use of COVID-19 Ads on Facebook - Silva, Márcio; Benevenuto, Fabrício (Proceedings of the Brazilian Symposium on Multimedia and the Web (WebMedia), 2020)
In view of the emergence of mobility restrictions and social isolation imposed by the coronavirus or COVID-19 pandemic, digital media, especially social networks, become a breeding ground for fake news, political attacks and large-scale misinformation. The impacts of this 'infodemic' can take even greater proportions when using sponsored content on social networks, such as Facebook ads. Using the Facebook ad library we collected more than 236k facebook ads from 75 different countries. Choosing ads from Brazil as the focus of research, we found ads with political attacks, requests for donations, doctors prescribing vitamin D as a weapon to fight coronavirus, among other contents with evidence of misinformation.